Governance and order-making in Central Asia: from illiberalism to post-liberalism?. Issue 3 (2nd July 2020) - Lottholz, Philipp; Heathershaw, John; Ismailbekova, Aksana; Moldalieva, Janyl; McGlinchey, Eric; Owen, Catherine
ABSTRACT: This forum brings together five different angles on the question as to whether and how political regimes and forms of order-making can and should be researched through the concept of 'illiberalism'. The discussion engages critically with this and associated concepts, such as 'illiberal peace' and 'authoritarian conflict management', which have been developed out of the Central Asian / Eurasian context and discussed in their wider global ramifications and, within the framing of 'illiberal peace', explored in various contexts in and beyond Central Asia. While further assessing the relevance and implications of this approach, this forum also attempts to think beyond 'illiberalism' by introducing and discussing the idea of 'post-liberalism'. This way, the authors engage in an exchange that serves to probe both concepts and to determine their strengths and limitations when it comes to analysing and understanding politics and societal processes in Central Asia.